Impact of Principal Leadership Styles on Teacher Job Performance: An Empirical Investigation - Parveen, Khalida; Quang Bao Tran, Phuc; Kumar, Tribhuwan; Shah, Akhter Habib (Frontiers in Education, 2022)
The present study is intended to investigate the relation and effect of principal leadership styles on teacher job performance at public secondary schools in Faisalabad city, Punjab, Pakistan. Given a correlational design purpose, data was assembled by drawing a sample of 102 principals and 512 teachers through self-administered questionnaires. The first instrument titled ‘Questionnaire for Principal Leadership Style’ (QPLS) comprises three sub-scales all reflecting high degree of internal consistency, namely autocratic leadership (α=.832), democratic leadership (α=.759), and laissez-faire leadership (α=.852). The second tool, Questionnaire for Teacher Job Performance (QTJP), also indicates good reliability (α=.813). Regarding the verification of the research questions and hypotheses, percentages, multiple regression, and Pearson’s correlation coefficient were subsequently performed at the significance level of p<.05. As the findings attest, 59.3% of variation in teacher job performance was statistically explained as the result of shared involvement of principal autocratic, democratic, and laissez-faire leadership styles. The results also revealed the autocratic leadership constituted the largely exercised style, significantly exerting a strong and positive impact on teacher job performance, while the laissez-faire leadership style impacted either problematic or unhelpful. Ultimately, the findings suggest that the principals under study should leverage a wise integration of leadership styles according to specific circumstances of their respective schools.